Influence of exothermic composition makeup on the AK7 alloy crystallization ranges - Tomash, Lipensky (Литьë и металлургия)
The article describes changing of the range of the α-phase and (α+β) eutectic crystallization temperatures, as well as of the beginning of the α-phase crystallization and beginning of (α+β) eutectic crystallization of the AК7 alloy as a result of treatment of the alloy with mixtures producing exothermic effect.